Isolation and characterization of gum from agathis borneensis - Aini Faizi, Jaslan. (Universiti Malaysia Sarawak (UNIMAS), 2004)
Studies were conducted to determine the physico-chemical properties and organic compound of gum from Agathis borneensis. The proximate compositions studied include percentage of moisture, ash, nitrogen and protein. The results showed moisture and ash content of 1.76% and 2.2%, respectively. Nitrogen content is lower compared to standard specification of nitrogen from Joint Expert Committee and Food Additives, JECFAlFAC, which is only about 0.23%. Percentage of protein is about 1.31%. Isolation and identification of organic compound was carried out by extraction, thin layer chromatography fractionation and subsequently analyzed on Gas Chromatography/Mass Spectrometry. The organic component identified are arabinose, rhamnose, glucuronic acid, 2,6-dimethyltridecanenitrile, N-isopropyl-3-phenylpropanamide and &.azaspiro-2,5octa-4,7-diens-6-carboxylic acid. A consideration amount of arabinose provides an early indication to similarity to Arabic gum.